Religious education, the philosophy and the history of brazilian education - Santos, Danilo Nobre dos (Faculdade de Filosofia e Ciências, 2019)
We intend to analyze the problem of Religious Education in its legal and curricular aspects in the history of Brazilian education through its methodological structuring, as well as its processes of constitution, identification and interaction of its themes in different educational contexts. In addressing this problem, we identify diverse and sometimes disparate economic and political interests, disperse opinions, discussions and trends, as well as judgments about some practices, as well as a lack of information regarding this topic and its conceptualization, also refers to the reality itself and the need of the learners. We consider the legal and curricular aspects of Religious Education to be a delicate and complex subject, but at the same time pertinent and of interest for the understanding of the history of Brazilian education itself, making it necessary to properly deepen the legislation on it, in order to contribute for a real clarification as to the possible reductions that may occur around the study of religious phenomena, discourse about God and the cultural-religious experience of a people. In this way, our intention is based on the observation of the links between education and religious doctrine and to what extent the legal and curricular contents adopted up to the present moment, considering all the reforms promoted, contribute, reinforce or correct the disparities that may still be with the news of the Brazilian National Curricular Common Base.